PENGEMBANGAN BERAS ANALOG DENGAN MEMANFAATKAN JAGUNG PUTIH [Development of White Corn-Based Rice Analogues] - Santi Noviasari; Feri Kusnandar; Slamet Budijanto (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2013)
White corn can be utilized as a source of non-rice carbohydrate in the manufacture of rice analogues. The rice analogues with rice-like characteristics were produced by an extrusion technique. The aim of this research was to develop rice analogues from white corn and to evaluate their physicochemical and sensory properties. The study was conducted in several stages, i.e. preparation, formulation, and physicochemical and sensory properties evaluation. The physicochemical properties of rice analogues evaluated included proximate nutritional composition, dietary fiber concentration, cooking time, water loss rate, color, and whiteness percentage, while their sensory preferences were evaluated using hedonic scale test. The rice analogues made of Pulut Harapan and Lokal Purbalingga corns (4.34:65.66%) added with 30% sago starch, was found to be the most preferred. The moisture, ash, protein, fat, carbohydrate, and dietary fiber composition of this rice analog was 9.32, 0.38, 6.86, 1.22, 91.54, and 5.35%, respectively.